Greening Starbucks: Investigating the Relationship between Consumer Green Awareness and Purchase Intentions in Malaysia - Lee, Jocelyne; Lim, Sheue Hui; Batul, Atiba; Sharma, Brahmmanand; Singh, Kavita; Khor, Winnie; Raveendran, Kamini Devi A/P; Kong, Mei Ching; Kooli, Syrine; Pradhan, Samarth; Kee, Daisy Mui Hung (Journal of The Community Development in Asia, 2023)
Starbucks, a prominent player in the F&B industry, has integrated sustainability into its marketing strategies. Starbucks encourages environmentally and socially responsible behavior among customers. This research examines the impact of green awareness on consumer purchase intention. A survey was conducted with 120 Starbucks consumers in Malaysia, and the data was analyzed using SPSS. The findings reveal that environmental concerns, green price awareness, and social influence positively influence purchase intention. However, the study finds no significant association between green brand image, green products, and purchase intention. This research provides valuable insights into consumer perception of green awareness and its influence on purchasing decisions. It underscores the importance of genuine environmental action alongside marketing tactics. The study emphasizes the industry's role in advancing sustainable development aligned with the SDGs.